2011
DOI: 10.24908/pceea.v0i0.3643
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Enhancement and Evaluation of Graduate Attributes and Outcomes Through Student-Run Forums

Abstract: The evolution of a curriculum involves changes at many different levels such as daily changes to reflect questions or areas of interest of a particular class, improvements to an established course based on observations from the professor, or more significant changes to streams of courses at a departmental level, or adaptation to suggested accreditation guidelines such the recent new Canadian Engineering Accreditation Board (CEAB) graduate attributes and outcomes. Most educational institutions have means of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The data offer some valuable information, and it is suggested that departments triangulate them with other sources of available data. Alternate data include those from the student exit surveys [11][12] [13], student forums [14], Industry Forums [15], and the course curriculum graduate attribute maps that were produced for the purposes of accreditation. For example, at the same time this study was being executed, an explanatory case study was being conducted to examine fourth year engineering student perceptions of the CEAB graduate attributes in the Mechanical Engineering program [13].…”
Section: Next Stepsmentioning
confidence: 99%
“…The data offer some valuable information, and it is suggested that departments triangulate them with other sources of available data. Alternate data include those from the student exit surveys [11][12] [13], student forums [14], Industry Forums [15], and the course curriculum graduate attribute maps that were produced for the purposes of accreditation. For example, at the same time this study was being executed, an explanatory case study was being conducted to examine fourth year engineering student perceptions of the CEAB graduate attributes in the Mechanical Engineering program [13].…”
Section: Next Stepsmentioning
confidence: 99%
“…[4,5]. Student lead forums were held at University of Manitoba to obtain input on how to improve the programs [8].…”
Section: Introductionmentioning
confidence: 99%